2014
DOI: 10.1016/j.jmbbm.2013.08.025
|View full text |Cite
|
Sign up to set email alerts
|

The role of mode of delivery on elastic fiber architecture and vaginal vault elasticity: A rodent model study

Abstract: We report on an experimental study of the role of mode of delivery and pregnancy on the architecture of vaginal elastic fibers and vaginal vault elasticity in female Sprague-Dawley rats. In primiparous rats submitted to spontaneous or Cesarean delivery and virgin rats submitted to simulated delivery, the tortuosity of elastic fibers (defined as the ratio of length to end-to-end distance) was observed to decrease when measured two days to two weeks postpartum. In addition, the measured tortuosity of elastic fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 24 publications
3
34
0
Order By: Relevance
“…The vaginal vault of virgin rats was found to be stiffer than that of multiparous rats. These results, in conjunction with the measured tortuosity results, confirmed that the elastin fibers in the vaginal vault may significantly remodel due to pregnancy and parturition, contributing to tissue elasticity [64].…”
Section: Applied Mechanics Reviewssupporting
confidence: 74%
See 3 more Smart Citations
“…The vaginal vault of virgin rats was found to be stiffer than that of multiparous rats. These results, in conjunction with the measured tortuosity results, confirmed that the elastin fibers in the vaginal vault may significantly remodel due to pregnancy and parturition, contributing to tissue elasticity [64].…”
Section: Applied Mechanics Reviewssupporting
confidence: 74%
“…Several studies have shown that the onset of pregnancy, prolapse, and menopause can alter the structure of vaginal tissue [59,[61][62][63][64]. A study conducted by Downing et al [64] on the influence of pregnancy and mode of delivery on the elastic fiber architecture and vaginal vault elasticity in rats showed that the tortuosity of elastin fibers decreased when measured at 2 days postpartum compared to virgin vaginal tissue. After 2 weeks postpartum, the measured tortuosity was similar to virgin vaginal tissue, suggesting that the vaginal tissue undergoes structural remodeling to allow for events such as pregnancy and then returns to its prior state [64].…”
Section: Vaginamentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we evaluated MMP-9 as one downstream effector of TGF-β1, although other factors such as elastin may play a role in POP. We believe that optimal evaluation of elastin requires specialized approaches that could be done in future studies [23]. …”
Section: Discussionmentioning
confidence: 99%